A comparative cohort study of post-COVID-19 conditions based on physical examination records in ChinaResearch in context - Zhong Liu; Boqiang Hu; Tao Zeng; Cuiping You; Nan Li; Yongjing Liu; Jie Zhang; Chenbing Liu; Piaopiao Jin; Xiaoxi Feng; Jun Chen; Jinyan Huang (EBioMedicine)
Summary: Background: Coronavirus disease-2019 (COVID-19), caused by SARS-CoV-2 virus infection, is characterized as a multisystem disease, potentially yielding multifaceted consequences on various organs at multiple levels. At the end of 2022, over 90% of the Chinese population was infected by SARS-CoV-2 within 35 days because of adjustments to epidemic prevention and control policies. This short-term change provides an unprecedented opportunity for comparative studies on COVID-19 infection among large populations. Methods: In this study, the physical examination data of 136,713 people in the past three consecutive years was employed to study the impact of COVID-19. Standard physical examination data, comprising evaluations of nearly a hundred indicators, were investigated for a comprehensive assessment of COVID-19’s effect on human health. Findings: The results suggested that most indicators remained stable or changed within a permissible range after the COVID-19 outbreak in December 2022, but several specific indicators presented abnormal patterns of varying durations. There was an observed increase in the fraction of T-wave abnormalities during the outbreak, especially in people with chronic diseases such as hypertension, liver steatosis, and hyperglycemia. Interpretation: These findings highlighted the impact of COVID-19 on cardiovascular health and its potential interaction with chronic diseases. Funding: This work was supported by the National Key Research and Development Program of China (2019YFE0108100), the National Natural Science Foundation of China General Program (82270159, 82070147).